Nanoglass and Nanocrystallization Reactions in Metallic Glasses - Perepezko, John H; Gao, Meng; Wang, Jun-Qiang (Frontiers in Materials, 2021)
Strategies to change the properties of metallic glass by controlling the glass transition behavior and the crystallization are essential in promoting the application of these materials. Aside from changing the composition approaches to stabilize the glass and frustrate the nucleation and growth of crystals at a fixed glass composition are of special interest. For example, by an optimal annealing treatment a liquid-cooled Au-based metallic glass can achieve very high kinetic stability to yield a large increase in glass transition temperature of 28 K; this is 3-5 times larger than the increase usually reported. The measured enthalpy decrease is about 50% of the difference between the as-cooled glass and the equilibrium crystalline state and reaches the extrapolated enthalpy of the supercooled liquid. Similarly, the glass transition and crystallization behaviors of a Au-based nanoglass shows ultrastable kinetic characters at low heating rate (e.g. 300 K/s) compared to a melt-spun ribbon, which is attributed to the kinetic constraint effect of nanoglobular interfaces. The ultrastable kinetic behaviors disappear at high heating rate (e.g. 30,000 K/s) as the interface constraint effect disappears. These results indicate that the nanoglass microstructure can act to increase metallic glass stability and provide another mechanism for the synthesis of ultrastable glass. Beyond the stability behavior, nanocrystallized microstructures such as those that develop in marginal Al-based metallic glasses yield a high number density of Al-nanocrystals dispersed in the amorphous matrix that show an attractive combination of high strength and low density and are related to the action of spatial heterogeneities such as medium range order. The heterogeneous and transient nucleation effects are critical in the nanocrystallization reactions in Al-based metallic glasses and can be assessed by Flash DSC measurements which also provide a basis to understand the strong effect of minor alloying additions on the delay time for the onset of primary Al nanocrystallization. These developments open new opportunities to modify the stability and properties of metallic glasses and a potential strategy to develop bulk Al-based metallic glasses.